Exploring PtSO4 and PdSO4 phases: an evolutionary algorithm based investigation1. Issue 27 (21st July 2015) - Sharma, Hom; Sharma, Vinit; Huan, Tran Doan
<x xml:space="preserve">Abstract</x> New phases of PtSO4 and PdSO4 are identified and their pressure–temperature phase diagrams are constructed using ab initio calculations.